PENGARUH PERSEPSI HARGA, KUALITAS PRODUK, DAN CITRA MEREK TERHADAP KEPUASAN KONSUMEN DAN DAMPAKNYA PADA MINAT BELI ULANG PRODUK MIE INSTANT SEDAAP - Rahayu Lestari; Elwisam Elwisam (Jurnal Ilmu dan Budaya, 2019)
This research was conducted with the aim to prove the "Influence of Price Perception, Product Quality, and Brand Image to Consumer Satisfaction and Its Impact on Buying Interest of Sedaap Noodle Products in Depok and Tangerang". Sampling based on Accidental Random Sampling technique, as many as 100 respondents divided into several regions by using proportional random sampling as follows: Depok and Tangerang. The analytical technique used in the study using partial least square technique (PLS). The results concluded that: 1) Price perception does not affect customer satisfaction Mie Innstant Sedaap; 2) Product quality affects customer satisfaction Instant Sedaap Noodle; 3) Brand image does not affect consumer satisfaction Instant Sedaap Noodle; 4) Consumer satisfaction influence to consumer buy back interest of Instant Sedaap Noodle. Consumer satisfaction becomes the intervening variable to the consumer buy back interest of Instant Sedaap Noodle.